2010
DOI: 10.1190/1.3284048
|View full text |Cite
|
Sign up to set email alerts
|

Investigating fault shadows in the Niger Delta

Abstract: The stratigraphic evolution of the Niger Delta is dominated by a continuous stepwise progradation occurring during a major tertiary regressive phase that continues to the present. The successive phases of the delta growth form transient depobelts that are bounded by mega-structural growth faults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…These lower-than-normal velocity events in the absence of overpressure and anisotropy which has been accounted for by previous researchers in the study area (Dutta 2002;Aikulola et al 2010;Oni et al 2011;Kanu et al 2014) are regarded as short-path multiple reflection events. The presence of strong subsurface reflectors and contacts between geologic bodies of different seismic properties at the footwall of the main boundary fault (beyond 3 s twoway time) is suggested as the probable causes of this multiple effect.…”
Section: Discussion Of Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…These lower-than-normal velocity events in the absence of overpressure and anisotropy which has been accounted for by previous researchers in the study area (Dutta 2002;Aikulola et al 2010;Oni et al 2011;Kanu et al 2014) are regarded as short-path multiple reflection events. The presence of strong subsurface reflectors and contacts between geologic bodies of different seismic properties at the footwall of the main boundary fault (beyond 3 s twoway time) is suggested as the probable causes of this multiple effect.…”
Section: Discussion Of Resultsmentioning
confidence: 71%
“…Aikulola et al (2010) related these chaotic and distorted reflections beyond 3 s two-way time most especially, at the footwall of regional faults to the onset of overpressure. Kanu et al (2014) reviewed the velocity anisotropy considerations using different anisotropy eta values, supported by Zoeppritz's modeling and velocity model updates.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Secondly, velocity estimations within the shadow zone did not properly account for this lower than normal velocities during data processing and this is likely responsible for the curtain of noise observed in the shadow zone (Retailleau et al, 2012). Aikulola et al (2010) related chaotic and distortive reflections observed beyond 3 s at the footwall of regional faults in the delta exhibits lower than normal seismic velocities, and associated these to the onset of overpressure regimes. Oni et al (2011), in an onshore study in the Niger Delta, submitted that if anisotropy is taken into consideration and corrected during data preparation and enhancement, seismic imaging could be improved behind the fault.…”
Section: Discussionmentioning
confidence: 99%
“…Aikulola et al (2010) and Opara (2012) investigated overpressure as the possible cause of reflection distortions beyond 3s in Onshore Niger Delta. In a similar study, Oni et al (2011) and Kanu et al (2014) investigated seismic anisotropy as the possible cause of reflection distortions beyond 3s in Onshore Niger Delta.…”
Section: Introductionmentioning
confidence: 99%